Protocol-based perioperative antimicrobial prophylaxis in urologic surgeries: Feasibility and lessons learned - Aditya Prakash Sharma; Sudheer Kumar Devana; Girdhar S Bora; Ravimohan Suryanarayan Mavuduru; Balvinder Mohan; Neelam Taneja; Shrawan K Singh; Arup K Mandal (Indian Journal of Urology, 2019)
Introduction: Rational use of antibiotics and strict adherence to practice guidelines is essential to prevent antibiotic resistance. The best surgical prophylaxis protocol requires tailoring of the available guidelines in accordance to the local bacterial flora. We designed a protocol for surgical prophylaxis to check the rampant abuse of antibiotics in the department of urology and evaluated its feasibility. Materials and Methods: Patients admitted for elective major surgeries under a single unit of our department over a period of 5 months were included in the study. A protocol for antibiotic prophylaxis was designed based on the European Association of Urology guidelines and the local hospital antibiogram. Single-dose intravenous cefuroxime was administered to the patients undergoing clean and clean-contaminated surgeries. Extended protocols were formulated for contaminated surgeries. Postoperative course and complications were recorded. Effectiveness was defined as adherence to the protocol (without an addition or a change in antibiotic regimen) along with an uneventful postoperative course. Prospectively maintained data were analyzed using descriptive statistics. Results: Data of 277 patients were analyzed. The mean age was 48.37 ± 17.39 years and 27.1% had comorbidities. Majority of the surgeries were clean contaminated (81%), and 60.3% of the total were endoscopic. The protocol was effective in 89.5% of the patients (248/277). The failure rate was higher for the contaminated procedures (41.7%) (odds ratio – 6.43; confidence interval = 1.51–27.2, P < 0.001). Post-operative sepsis with or without shock was the commonest cause (16/29, 55.2%) of protocol failure. Fourteen out of the 16 patients who developed sepsis had undergone endourological surgeries. Conclusions: Protocol-based perioperative antibiotic prophylaxis in urological surgeries is feasible. Similar protocols should be developed and validated at other major centers to limit the unnecessary use of antibiotics and prevent the emergence of antibiotic resistance.